Long-term corticosteroid use and dietary advice: a qualitative analysis of the difficulties encountered by patient - Muriel Nogué; Jacques Rambaud; Sylvie Fabre; Nathalie Filippi; Christian Jorgensen; Yves-Marie Pers (BMC, 2019)
Abstract Background Nearly 1% of the population is currently treated with long-term corticosteroid therapy. When corticosteroids are introduced, information concerning potential adverse effects and recommendations for lifestyle changes aimed at preventing such effects is provided to patients. However, studies have shown patients often do not fully comprehend the information provided and have difficulty implementing the recommended dietary and physical activity advice. In this study, we aim to highlight the difficulties encountered by patients in comprehending and implementing recommendations in the context of long-term corticosteroid use. Such information can be used to better optimize care, particularly concerning adherence to the treatment, the diet, and thus improve the quality of life of patients. Methods We recruited adult patients under long-term corticosteroid (≥ 3 months, ≥ 5 mg/day) treatment from both general medicine and rheumatology practices. We performed a qualitative analysis based on semi-structured interviews of these patients. Transcripts of these interviews were then compiled and analysed using a thematic approach. Results Sixteen patients were included. Analysis of the interviews revealed that patients' hope for effective corticosteroid treatment was counterbalanced by concerns over potential adverse effects. In some patients, the need to respect a strict and imposed diet induced psychological distress, potentially leading to eating disorders or fear of social exclusion. Furthermore, patient ambivalence toward the therapeutic education was highlighted, as well as the notion of filtering information, conscious or unconscious, as revealed by their lack of recall. The relationship with the physician also affected the treatment experience. Conclusion Our analysis of the personal experience of patients regarding recommended lifestyle changes associated with long-term corticosteroid treatment highlights patient difficulties and suggests different ways of improving therapeutic education.